Effects of Herbal Extracts, Glycomacropeptides, and Probiotics on Urolithiasis Prevention: An Overview - Majidinia, Lida; Anbalagan, Muralidharan; Kalbasi-Ashtari, Ahmad; Wai, Wong Chen; Ranganathan, Venkatalakshmi; Panneerselvam, Jithendra; Chinnappan, Sasikala; Mani, Ravishankar Ram (Current Traditional Medicine, 2026)
Urolithiasis, a prevalent and recurrent disorder, imposes a significant global health burden. Conventional treatments often fail to prevent recurrence, prompting interest in nutraceutical interventions. This review explores the therapeutic potential of herbal extracts, glycomacropeptides (GMP), and probiotics in preventing kidney stone formation. Herbal medicine inhibits calcium oxalate (CaOx) crystallization, modulates urinary biochemistry, and mitigates oxidative stress via bioactive phytochemicals. Probiotics, particularly Oxalobacter formigenes, Lactobacillus, and Bifidobacterium species, regulate oxalate metabolism and enhance gut-kidney axis function, reducing urinary oxalate excretion. GMP, a bioactive milk-derived peptide, offers renoprotective effects by minimizing uremic toxin production, alkalinizing urine, and modulating gut microbiota. Integrating these nutraceuticals into urolithiasis management may reduce stone recurrence, improve renal function, and serve as viable adjuncts to conventional therapies. This review synthesizes recent clinical, in vivo, and in vitro findings, emphasizing their mechanisms, efficacy, and translational potential in nephrolithiasis prevention.
Keywords: probiotics